Scientific Production And Dissemination Forecast Related With Covid-19 (Journal of Pharmaceutical Negative Results, 2023)
The new coronavirus SARS-CoV-2 cuases the known disease as COVID -19 extended around the world, increasing the infected and deceased cases. It was declared pandemic by OMS in March of this year. It is reason to actívate the scientific community in the production and dissemination of scientific articles. This paper analyzes and predicts scientific publications related with COVID 19, monthly and for country, proceeded and registered daily by CTS Observatory based on PubMed. USA highlights as the main country who publishes with 7,974 (27.73 %) results, followed by China with 4,202 (14.61 %). In Iberoamerican level, Spain and Brazil highlight with 4.26% y 2.37%, respectively. An increase of publications related with COVID-19 of 2,236 monthly publications is predicted in the mentioned database.